Three-Tiered Controller for Obstacle Avoidance in a PV Panel-Powered Wheeled Mobile Robot: Considering Actuators and Power Electronics Stages - Erik Reyes-Reyes; Benjamin Natanael Santiago-Nogales; Ramon Silva-Ortigoza; Magdalena Marciano-Melchor; Jose Rafael Garcia-Sanchez; Angel Adrian Orta-Quintana; Gilberto Silva-Ortigoza; Hind Taud; Miguel Hernandez-Bolanos (IEEE Access)
This research addresses the obstacle avoidance problem in wheeled mobile robots powered by renewable energy by considering all subsystems involved. A three-tier hierarchical controller is developed, integrating the technique of artificial potential fields. The proposed controller incorporates the dynamics of the three key subsystems typically found in a wheeled mobile robot: The mechanical structure, actuators, and power electronics. At the highest tier, input-output linearization is combined with artificial potential fields. The medium tier employs two controllers based on differential flatness theory, while the lowest tier incorporates sliding mode control and proportional-integral control. The effectiveness of the control strategy is experimentally validated using a differential drive-type wheeled mobile robot prototype, leveraging the TDK-Lambda G100-17 as a renewable energy emulator, along with the DS1104 board and Matlab-Simulink software. Experiments were conducted under two scenarios: a) the emulation of a commercial photovoltaic panel to simulate realistic operating conditions and b) the application of time-varying input voltages to replicate dynamic power source variations. The experimental results demonstrate the robustness of the proposed controller against sudden changes in system parameters, confirming its reliability and effectiveness.